Structure activity relationships of novel and selective beta1-adrenoreceptor ligands - Mistry, Shailesh N. (2009)
Of the numerous l3-blockers clinically available to treat conditions such as angina pectoris, hypertension and heart failure, none possess antagonist activity specific to the beta1-adrenoceptor. Those described as 'cardioselective', such as nebivolol and bisoprolol, generally show less than 50-fold beta1/beta2-selectivity, which can be lost at higher doses. Others, such as propranolol and sotalol are actually more beta2-selective. Overall, a degree of concomitant beta2-adrenoceptor blockade (risking compromised respiratory function and loss of peripheral vasodilatation) by current therapeutic agents precludes their use in patients with disorders such as asthma and peripheral vascular disease. This project aims to develop novel molecules with much improved beta1/beta2-selectivity over current beta1-blocker therapy as well as improving knowledge of ligand-receptor interaction at the beta1-adrenoceptor, through an analogue-based drug discovery approach. A highly selective or specific beta1-adrenoceptor antagonist is likely to cause fewer side-effects and be suitable for use in previously contraindicated disease states. This thesis reports the design, synthesis and pharmacological data (provided by Dr. Jillian Baker) of a library of novel ligands for the beta1- adrenoceptor, based upon the lead compound LK 204-545. LK 204-545 was selected based on reported high potency at the beta1-adrenoceptor as well as good beta1/beta2-selectivity. Modification of various motifs on structures derived from LK 204-545 allowed the generation of new structure-activity relationships and ultimately afforded the highly 131-adrenoceptor selective compound, 1-(2-(3-(4-(2-(cyclopropylmethoxy)ethoxy)phenoxy)-2-hydroxypropyl amino)ethyl)-3-(4-hydroxyphenyl)urea hydroformate (12Sc). This compound acted as a highly-selective beta1-adrenoceptor antagonist in a pilot in-vivo study in the regional hemodynamic rat model (carried out by Prof. Sheila Gardiner).